Pengembangan Media Pembelajaran Interaktif Berbasis Articulate Storyline 3 untuk Meningkatkan Hasil Belajar Siswa - Hanny Firstanianta; Meirza Nanda Faradita; Ishmatun Naila (Journal on Education, 2023)
The purpose of this study is to produce a new product or improve an existing product to make it more effective and relevant, as well as describe the validity, practicality and effectiveness of interactive learning media based on articulate storyline 3. The method used is Research and development (R&D). The research findings showed that interactive learning media based on articulate storyline 3 got a score for material validity of 88.7% with valid criteria while the validity of media experts got a score of 87.5% with valid criteria. Students carried out a trial of learning outcomes tests which obtained an average score of 80 with effective criteria that are meaningful above from the school's KBM (Minimum Learning Completion). Based on the results of the study, it was concluded that interactive learning media based on articulate storyline 3 on the material of the solar system as a whole met the criteria of valid, practical & effective. Researchers believe that this developed learning media can be a solution in the development of interactive learning media that makes it easier for students, especially on solar system materials.